2011
DOI: 10.1037/a0022339
|View full text |Cite
|
Sign up to set email alerts
|

mGluR5 positive allosteric modulation enhances extinction learning following cocaine self-administration.

Abstract: Extinction of classically and instrumentally conditioned behaviors, such as conditioned fear and drug-seeking behavior, is a process of active learning, and recent studies indicate that potentiation of glutamatergic transmission facilitates extinction learning. In this study we investigated the effects of the type 5 metabotropic glutamate receptors (mGluR5) positive allosteric modulator 3-cyano-N-(1,3-diphenyl-1H-pyrazol-5-yl)benzamide (CDPPB) on the extinction of cocaine-seeking behavior in rats with a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 66 publications
(82 reference statements)
7
65
2
Order By: Relevance
“…In addition, extinction of fear and drug memories represents a simpler form of flexibility entailing the formation of a new memory that competes with the original drug or fear memory. In agreement with previous studies showing that CDPPB can facilitate the extinction of cocaine memories (Cleva et al , 2011; Gass et al , 2009), we observed that CDPPB facilitates the extinction of ethanol self-administration, including the reversal of resistance to extinction observed in adult AIE exposed rats. In light of the fact that both set shifting and extinction are critically-dependent on intact medial PFC function, our results suggest that the procognitive actions of CDPPB relate, at least in part, to actions within the PFC that enhance cognitive control of behavior.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, extinction of fear and drug memories represents a simpler form of flexibility entailing the formation of a new memory that competes with the original drug or fear memory. In agreement with previous studies showing that CDPPB can facilitate the extinction of cocaine memories (Cleva et al , 2011; Gass et al , 2009), we observed that CDPPB facilitates the extinction of ethanol self-administration, including the reversal of resistance to extinction observed in adult AIE exposed rats. In light of the fact that both set shifting and extinction are critically-dependent on intact medial PFC function, our results suggest that the procognitive actions of CDPPB relate, at least in part, to actions within the PFC that enhance cognitive control of behavior.…”
Section: Discussionsupporting
confidence: 93%
“…In light of the fact that both set shifting and extinction are critically-dependent on intact medial PFC function, our results suggest that the procognitive actions of CDPPB relate, at least in part, to actions within the PFC that enhance cognitive control of behavior. Importantly, the ability of CDPPB to reverse behavioral deficits induced by AIE does not appear to result from alterations in locomotor activity as previous research in our laboratory (Cleva et al , 2011) and others (Kufahl et al , 2012; Reichel et al , 2011) has shown that this dose of CDPPB does not alter motor behavior.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In monkeys, mGluR5 antagonist administration attenuates cocaine self-administration, cocaine-induced reinstatement of drug seeking behavior, and the discriminative stimulus effects of cocaine (8, 9). However, recent studies in rodents have also shown that activation of the mGluR5 improves the acquisition and consolidation of extinction learning following cocaine exposure (10, 34). Thus, while these studies show that mGluR5 antagonism reduces cocaine self-administration in animal models, activation of the receptor appears to improve extinction learning.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of an mGluR5 antagonist to rodents reduces the reinforcing properties of cocaine (27) and similar results have been reported in rhesus monkeys (8, 9). On the other hand, activation of the mGluR5 with the administration of a positive allosteric modulator has been shown to improve extinction learning following cocaine self-administration in rodents (10). …”
Section: Introductionmentioning
confidence: 99%